Interleukin-1 is essential for systemic inflammatory bone loss. Issue 01 (5th February 2009) - Polzer, K; Joosten, L; Gasser, J; Distler, J H; Ruiz, G; Baum, W; Redlich, K; Bobacz, K; Smolen, J S; van den Berg, W; Schett, G; Zwerina, J
Abstract : Objectives: Chronic inflammation is a major risk factor for systemic bone loss leading to osteoporotic fracture and substantial morbidity and mortality. Inflammatory cytokines, particularly tumour necrosis factor (TNF) and interleukin-1 (IL1), are thought to play a key role in the pathogenesis of inflammation-induced bone loss, but their exact roles are yet to be determined. Methods: To determine whether TNF directly triggers bone loss or requires IL1, human TNFα mice (hTNFtg) were crossed with mice lacking IL1α and IL1β (IL1 −/− hTNFtg). Systemic bone architecture was evaluated using CT scanning, static and dynamic bone histomorphometry and serum markers of bone metabolism. Results: hTNFtg mice developed severe bone loss accompanied by a severe distortion of bone microarchitecture. Bone trabeculae were thinner and decreased in numbers, resulting in increased trabecular separation. Histomorphometric analyses revealed strongly increased bone resorption in hTNFtg mice compared with wild-type mice. In contrast, IL1 −/− hTNFtg mice were fully protected from systemic bone loss despite still developing inflammation in their joints. Lack of IL1 completely reversed increased osteoclast formation and bone resorption in hTNFtg mice and the increased levels of RANKL in these mice. Structural parameters and osteoclast and osteoblast numbers were indistinguishable from wild-type mice. Conclusions: These data indicate that IL1 is essential for TNF-mediated bone loss. Despite TNF-mediated inflammatory arthritis, systemic bone is fully protected by the absence of IL1, which suggests that IL1 is an essential mediator of inflammatory osteopenia.